Analisis Pertumbuhan Aset, Dana Pihak Ketiga dan Pembiayaan Perbankan Syariah Pasca Covid-19 - Izzaturrahman, Muh. Dzulfikar (CV. Civiliza Publishing, 2023)
Introduction/Main Objectives: This research aims to analyze the growth of asset variables, third party funds and financing distributed by sharia banking in the post-Covid-19 pandemic period. Research Methods: The method used in this research is descriptive qualitative using secondary data from OJK sharia banking statistical reports. Finding/Results: The results of this research indicate that assets, third party funds and total financing disbursed by sharia banking continue to experience positive growth in the post-Covid-19 pandemic period. At the end of 2022, sharia banking recorded asset growth of 15.63% (yoy), growth in third party funds of 12.93% (yoy), and growth in disbursed financing of 20.44% (yoy). Conclusion: This growth indicates that public trust in sharia banking is increasing and sharia banking is able to survive the crisis caused by the Covid-19 pandemic.